NILAI KEIMANAN DALAM SASTRA SUFISTIK TERNATE: SUATU KAJIAN KETASAWUFAN - Halil, Muamar Abd.; Abasa, Rafik; Abdullah, Taib (Cakrawala Bahasa, 2025)
The purpose of this study is to describe the Faith Values of Ternate Sufi Literature, using the theories of Sufism, Meaning, Values, and Sufism. The method used in this study is descriptive with a qualitative approach. This study takes Ternate Sufi literature as its object of study by looking at the elements of Sufism contained therein. Ternate Sufi literature has deep meanings in accordance with the teachings of the Qur'an and Hadith. Values are the essence of life, which are born from agreed-upon culture and norms. The results of this study found that there are 3 values contained in Ternate Sufi literature, namely; 1) Faith Values, 2) Worship Values (Shari'ah), and 3) Moral Values. However, what is analyzed is the Faith Value. This classification is based on the explanation of the Prophet Muhammad SAW to the Angel Gabriel regarding the meaning of Faith, Islam, and Ihsan which are essentially the same as faith, sharia and morals.